Applications and Challenges of Blockchain Technology in Agriculture Sector: A Review - Deshmukh, Sagar; Patil, Sharvari (Journal of Agricultural Extension Management, 2022)
Technology plays an important role in the growth of the country. New technologies are helping people in doing the tasks more effectively by saving time, money and effort. Information, Communication and technology helped to push the stagnant growth of Indian industries. In agriculture, dissemination of information has helped people to acquire knowledge of farming activities, sharing needs, access to the market through TV and radio. As technology is evolving, Artificial Intelligence, Machine learning, Deep learning have paved the way in the agriculture sector. Simultaneously, the Government of India took up the initiative of establishing and supporting 10,000 Farmer Producer Organizations to strengthen the farming community and the Indian agriculture sector. In making the initiative successful, apt deployment and use of technology will play a critical role. In this article, the authors have discussed, what blockchain technology is, its applications and challenges in the agriculture sector.